Pelatihan Penggunaan Aplikasi Mendeley bagi Mahasiswa dalam Membuat Sitasi Karya Ilmiah di Amikom Resource Centre Yogyakarta - Susilawati, Ida; Labibah, Labibah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This Mendeley training aims to facilitate students in making scientific work citations on assignments, theses, theses and so on. The method used to make this training there are three stages, namely the pre-training, on-going training and post-training stages. The result of this paper is that using Mendeley as an application to create written citations makes it very easy for all people, both students and other writers. Mendeley itself is a free software that was created to manage various research and can be used as a data store. In this training, 25 students from Amikom University took part in the Mendeley training. There were two materials that were presented and practiced, namely Mendeley Desktop and Mendeley Reference. Both Mendeley have a number of features in common, but currently most students use Mendeley Reference.